Fenologia e diversidade genética entre acessos de Clotropis procera(Ait.) W.T. Aiton baseada em caracteres agronômicos e bromatológico - Almeida, Isaias Vitorino Batista de (2017)
Calotropis procera (Ait.) W.T. Aiton is a perennial and xerophilous species with crop potential for forage production in the Brazilian semi-arid region. Due to its economic importance, the aim was to evaluate phenology and genetic diversity among C. procera accessions through agronomic and bromatological characteristics. Seeds of 70 accessions of C. procera were collected between october of 2015 and january of 2016, in areas of natural occurrence of the species in the Northeast region of Brazil. Currently these accessions make up the germplasm collection of the National Institute of the Semi-arid (INSA). The experiment was conducted in a greenhouse in the INSA, in Campina Grande - PB, between january and september 2016. The plants were cultivated in plastic pots with capacity of 10 liters, filled with soil, where the fertilization was done according to soil analysis and recommendation, and were irrigated every 3 days. In the phenology study, the morphophysiological characteristics were evaluated every 30 days, beginning at 30 days after sowing (DAS) and ending at 240 DAS. Physiological indexes were estimated up to 120 DAS and leaf fall, flowering and fruiting were evaluated. Obtained the mean of each characteristic with the adjustment and selection of regression models to explain the growth of C. procera based on the coefficient of determination. The vegetative stage of C. procera occurs during the 240 DAS, with fall and production leaf continuously, while the reproductive stage begins at 153 DAS, pursuing until 222 DAS, depending on the accession, making constant issuing of inflorescences on plants after the beginning of flowering.In the study of genetic diversity by agronomic characters, the experimental design was a randomized block with three replicates and data from 23 traits were used, and there was a significant difference (p <0.01) for the F test in all characters, where the genetic parameters estimates proved the genetic effect on the characters expression, with high heritability (h2) estimates of high magnitude. In addition, the analysis of Canonic Variables and grouping by the Tocher and UPGMA methods (Unweighted Pair Group Method with Arithmetic Mean) was performed. Phytomass characteristics are the main contributors to genetic divergence in C. procera genotypes. In the research of genetic divergence based on the bromatological composition, the plants were collected at 120 DAS, and the following production characteristics xii were obtained: stem fresh mass, leaf fresh mass, total fresh mass, stem dry mass , leaf dry mass and total dry mass. In addition, dry matter, mineral matter, organic matter, crude protein, ethereal extract, neutral detergent fiber, acid detergent fiber, total carbohydrates and non-fibrous carbohydrates were determined. The principal components analysis was obtained by grouping by the Tocher method and UPGMA based on these characters. All the production characteristics and the bromatological composition, with the exception of acid detergent fiber, contribute to the genetic divergence of C. procera accessions. There is genetic variability among the 70 accessions of C. procera based on agronomic and bromatological characters. Accessions 1, 12, 20, 39, 48, 50, 57, 67 and 70 are promising in the breeding program of C. procera, with agronomic and forage potential, and can be used as parents in hybridization programs and indicated to compose future studies.